Filmski turizem in turizem popularne kulture - Turnšek, Maja (University of Maribor Press, 2022)
Film Tourism and Popculture Tourism.The monograph critically reflects on current research in film tourism and popular culture tourism. Simplified, we can distinguish amongst four main approaches to researching these phenomena according to their central research question, reflecting the differences in theories and research methods applied: (a) What effects do the media have for tourists? (b) How do the (potential) tourists use films and popular culture? (c) What is the active role of film tourism destinations in relation to pop culture industry and tourists? And finally (d) How to analyse the complex interdependence between media, tourists, and the destination? Through an in-depth analysis of the approaches and related plethora of theories, the author reflects on the blind spots in the current research and theoretical imagination of film tourism. Throughout the monograph, she defends the thesis that local tourism communities are not only passive and powerless recipients of media content, but active co-creators in the place-making processes. The analysis of film tourism and popular culture tourism must thus necessarily include the social construction of space and the active role of destination management in this process.